TINJAUAN YURIDIS TERHADAP PERKARA PERMOHONAN PEMBATALAN PERKAWINAN DI PENGADILAN AGAMA (STUDI KASUS PUTUSAN PENGADILAN AGAMA LEBONG NOMOR: 0059/PDT.G/2015/PA.LBG.) - Sudarmadi, Sudarmadi (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2017)
Marriage in Indonesia is regulated in Law no. 1 of 1974 concerning marriage, and  Government Regulation  of the Republic  of Indonesia No. 9 of 1975 on the  Implementation of Act No.1 of 1974. then  for the  people of Islam  also apply Presidential Instruction No.1 Year 1991 on Compilation of Islamic Law as a complement of the Law No. 1 Year 1974. In the case of the position of this research object, that the applicant as a woman (wife) feels never divorced with her husband. However, her husband believes  that she has divorced  her, so the husband marries  another woman. So the wife declared the marriage illegitimate, because it violates the provisions, namely when the husband is married to the second wife, the husband did not ask permission to the first wife, in addition  to no permission of polygamy from the Religious Courts. So the first wife applied for a cancellation of marriage to the Religious Court in order  for the second marriage to be canceled. The type of research used  is qualitative research, which referred to qualitative research is a research procedure that produces descriptive data in the form of words  or verbal from the people and behavior  observed. Based on the formulation of the problem and research objectives, the  approach method used  is the  juridical  approach. Juridically this research may  include  research on legal principles,  legal system,  legal synchronization, legal history, and  comparative law. Research location  at Lebong  Religious Court. The data used in this study consist of primary data and secondary data. The data obtained from both the literature  and the interview will be analyzed by using qualitative analysis method, a research procedure that produces analytical descriptive data.  The result  of the  research found  that the  judges  of Lebong  Religious Court on Marriage Cancellation with decision number 0059 / Pdt.G / 2015 / PA Lbg was rejected by the panel  of judges so that the marriage of the Plaintiff’s husband with the Defendant was still legally valid and the Defendant still got his wife rights. In the contents of the decision filed a petition for the cancellation at the Lebong Religious Court, which was then registered in the case  Number  0059 / Pdt.G / 2015 / PA.Lbg. which consists  of three  judges did not all agree  with the decision. One judge argued  differently from the majority of judges. Opinions differ from minority judges included in the content of the verdict called dissenting opinion.